(untitled) (Филолошке студије, 2021)
The contemporary challenges of culture and gender in consumer society are numerous. Through critical reflections on certain aspects of women’s representation in popular culture, we will re-examine her role in society, seeking explicit and subliminal sexist messages embedded in literary and film language. Exploring the hegemony of the body, through the objectification of women and sexism, the cultural shackles of normative femininity, we will try to find gender asymmetry in the media representation and note the relationship with the ideology of consumerism and mass culture. Decoding the gender stereotypes, on the one hand, and the contemporary post-feminist transformations of femininity, on the other, we will re-examine the gender roles in popular culture by asking questions: To what extent do books and films about Bridget Jones and The Stepford Wives oppose the macho, sexist and patriarchal culture? Are they a rebellion against gender and structural discrimination against women? Is the criticism in those works clear and explicit or, in the attempt to detect gender stereotypes, do they in fact legitimize and strengthen them? Is it a matter of subversion, resistance or acceptance, or is it a reconciliation with the dominant values ​​of popular culture and masculine society? Through the polysemic reading of the texts we will seek for the new meanings that are created through the juxtaposition of the code and the decoder, in the interaction between the text, the meaning, the context, the recipient and the discourse. The production of meanings extends far beyond the processes of fabrication, exchange and reproduction of culture.